Evaluation of fundamental properties of compacted mixes used as patching materials for low volume roads - Ismail, Che Ros; Hainin, Mohd. Rosli; Chik, Abdul Aziz (Faculty of Civil Engineering, 2005)
Patching is one of the most common maintenance tasks carried out on low/medium volume roads in Malaysia. It is a technique of treating pavement distresses such as potholes and cracks. Failure of patched road is now becoming a burden to the responsible authority since a lot of money has been spent for repatching the same area of distresses. No appropriate guideline for patching works, mainly in terms of compaction effort and mixes is the reason for patching failure. Beside that, the selection of appropriate maintenance method also needs to be considered to ensure that the road can be repaired effectively. In this study, hot and cold mixes were used. The hot mixes used were ACW20 and BMW14, whilst cold mixes were IKRAMIX and SSMIX. The laboratory experiments conducted were Compaction, Bulk Specific Gravity, Stability and Flow, Permeability, Tensile Strength, Bitumen Extraction and Sieve Analysis. All tests were carried out according to standard requirement, JKR/SPJ/1988. from this study, it was found that hor mixes are most suitable to be used as road patching material. Besides having lower permeability and non-porous, they also have higher tensile strengths.